Win-Win: Advancing Written Language Knowledge and Practice through University Clinics - Katz, Lauren A.; Fallon, Karen A. (Seminars in Speech and Language, 2015)
Speech-language pathologists (SLPs) are uniquely suited for assessing and treating individuals with both spoken and written language disorders. Yet as students move from the elementary grades into the middle and high school grades, SLPs tend to provide fewer direct language services to them. Although spoken language disorders become written language disorders, SLP are not receiving sufficient training in the area of written language, and this is reflected in the extent to which they believe they have the knowledge and skills to provide services to struggling readers and writers on their caseloads. In this article, we discuss these problems and present effective methods for addressing them.
Keywords: Written language; language-based learning disability (LLD); personnel preparation